DINAMIKA STATUS HUKUM BADAN USAHA MILIK DESA DI INDONESIA - Arta, I Komang Kawi; PRATAMA, I PUTU ANDIKA; Wira Sena, I Gede Arya (Jurnal Yustitia, 2024)
There is no legal basis that covers the existence of BUMDes in villages, considering that BUMDes are businesses that are able to support the economy in the village. It is necessary to know the development of existing regulations in Indonesia that underlie the existence of BUMDes. The research method used is normative juridical using a statutory approach and a conceptual approach. The results show that the first development started from the birth of Law Number 8 of 2005 concerning amendments to Law Number 32 of 2004 concerning Regional Government, as mandated in Chapter VII, part five, which states that Village Governments can establish Village-Owned Enterprises in accordance with village needs and potential with the hope of increasing community and village income. As a follow-up to the implementation of the establishment of BUMDes, based on article 78 of PP 72 of 2005 concerning Villages, it is explained that the Regency/City Government needs to establish Regional Regulations (PERDA) concerning Procedures for the Establishment and Management of Village-Owned Enterprises (BUMDes). Minister of Home Affairs Regulation No. 39 of 2010 can be interpreted as the main thing that provides direction on how to form and manage BUMDes so that they can be in accordance with the expected objectives in order to support village income and contribute to the welfare of the village community within it. Government regulation number 46 of 2014 concerning Implementing Regulations of Law Number 6 of 2014 concerning Villages, as well as determining the legality of BUMDes through village regulations. This regulation does not imply that the BUMDes must be a legal entity. However, in development there is not a single regulation that regulates BUMDes as village-owned business entities with legal entities, both before and after the issuance of government regulation number 46 of 2014 concerning Implementing Regulations of Law Number 6 of 2014 concerning Villages. The enactment of Law Number 11 of 2020 concerning Job Creation means that the legal status of BUMDes is a legal business entity and Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises, was issued to implement the provisions of Article 117 and Article 185 letter b of Law Number 11 of 2020. 2020 concerning Job Creation.